2014
DOI: 10.1186/1471-2407-14-85
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200a inhibits epithelial-mesenchymal transition of pancreatic cancer stem cell

Abstract: BackgroundPancreatic cancer is one of the most aggressive cancers, and the aggressiveness of pancreatic cancer is in part due to its intrinsic and extrinsic drug resistance characteristics, which are also associated with the acquisition of epithelial-to-mesenchymal transition (EMT). Increasing evidence suggests that EMT-type cells share many biological characteristics with cancer stem-like cells. And miR-200 has been identified as a powerful regulator of EMT.MethodsCancer Stem Cells (CSCs) of human pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 42 publications
5
64
0
Order By: Relevance
“…Down-regulation of miR-200a has been shown to be linked with EMT phenotype. For example, Xia [47]. Consistently, our data showed that miR-200a expression was significantly decreased in LCSCs and reexpression of miR-200a reversed EMT to MET phenotype.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Down-regulation of miR-200a has been shown to be linked with EMT phenotype. For example, Xia [47]. Consistently, our data showed that miR-200a expression was significantly decreased in LCSCs and reexpression of miR-200a reversed EMT to MET phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…It has been emerged that EMT was associated with cancer invasion and metastasis, drug resistance, and can generate cells with properties of stem cells. According to recent reports, CSCs often exhibits EMT phenotype in several human malignancies, such as breast cancer [23], pancreatic cancer [47], and prostate cancer [48]. Here, we found that EMT phenotype was also occurred in LCSCs.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, further investigations into the mechanisms by which DCLK1 regulates Bmi-1 in human cancers are necessary to increase our knowledge of the way cancer progression is regulated. Moreover, we found the high DCLK1 subtype to be strongly enriched for EMT pathway genes as well as miR-200 and let-7 targets, both of which have been reported to be EMT inhibitors [35,48,49]. Therefore, the study presented here provides strong evidence that DCLK1 silencing could inhibit Bmi-1 expression and EMT, which may be one of the molecular mechanisms by which DCLK1 facilitates cancer metastasis.…”
Section: Discussionmentioning
confidence: 51%
“…It has also been associated with worse survival in prostate carcinomas [26]. Conversely, in pancreatic cancer, miR-200a has been reported to suppress EMT, proliferation, and invasion in vitro, by down-regulating DEK protein at least [27-29]. The results of a small study with 11 patients suggested that miR-200a may be overexpressed in cancer tissue when compared with samples from benign pancreas [30].…”
Section: Discussionmentioning
confidence: 99%